(untitled) (Trabalho & Educação, 2016)
This article aims to identify the activities and cultural manifestations related to leisure, present in the educational processes and experienced within Vocational and Technological Education schools (EPT schools) in Brazil. The basis for this work was the definition and analysis of the established relationships between education, leisure and work within these schools, taking as object of study the activities and cultural manifestations related to leisure identified in the school routine. For this, it was considered the materialistic dialectic as a research principle, considering the Brazilian academic production on the proposed problematic, particularly in relation to leisure studies and curriculum studies, as well as the access to documents and information, printed and / or electronic, of the schools. The immersions in school routine in two schools of the Professional Education Science and Technology Federal Network, in Brazil, through the techniques of direct observation and semi-structured interviews have revealed some particularities. Several alternatives to approach the knowledge in the educational processes of the surveyed schools are implemented by the initiative of students, including theater, music and cinema activities, among others, conferring to school work an "informal character of" that does not seem possible in the more formal processes adopted in such schools. This "informal character of", which indicates close relationships with leisure, suggests a significant amplification in the learning opportunities, which can also be observed in some changes in the pedagogical practice of teachers, in their work, and in the leading of the formative processes of mid-level technical education courses. The activities and cultural manifestations related to the leisure and incorporated into the educational processes of the surveyed schools have indicated the possibility to understand them as something that runs through the space, the time and micro times of human life. Given the conditions of which results in leisure that we have today in the social formation in which we live, the indicatives point in the direction that the people think, project, create and enlarge the boundaries of their time and their leisure experimentation spaces, giving new meaning to something that does not seem fit merely under this denomination anymore. ___ Este artigo tem como objetivo identificar as atividades e as manifestações culturais relacionadas ao lazer, presentes nos processos educacionais e experimentadas no interior de escolas de Educação Profissional e Tecnológica (escolas de EPT). A base para isso foi a delimitação e a analise das relações estabelecidas entre educação, lazer e trabalho no interior dessas escolas, tomando por objeto de estudo as atividades e as manifestações culturais relacionadas ao lazer identificadas no cotidiano dessas escolas. Para isso, lançou-se mão da dialética materialista como princípio de pesquisa, considerando-se a produção acadêmica brasileira relativa à problemática proposta, particularmente em relação aos estudos do lazer e aos estudos curriculares, além do acesso a documentos e informações, impressos e/ou eletrônicos, das escolas investigadas. As imersões no cotidiano escolar de duas das escolas da Rede Federal de Educação Profissional, Científica e Tecnológica, por meio da observação direta e de entrevistas semiestruturadas, revelaram que algumas das alternativas de trato com o conhecimento nos processos educacionais das escolas pesquisadas são implementadas por iniciativa dos alunos, com atividades de teatro, música e cinema, entre outras, conferindo ao trabalho escolar um “caráter informal” que não parece possível nos processos mais formais adotados em escolas desse tipo. Esse “caráter informal”, que indica relações estreitas com o lazer, sugere uma ampliação significativa nas possibilidades de aprendizado, o que também pode ser observado em algumas mudanças na prática pedagógica dos professores, no seu trabalho e na condução dos processos formativos de cursos de formação técnica de nível médio. As atividades e manifestações culturais relacionadas ao lazer e incorporadas aos processos educacionais próprios das escolas pesquisadas indicaram a possibilidade de entendê-las como algo que atravessa os espaços, os tempos e os microtempos da vida humana. Dadas as condições das quais resulta o lazer que temos hoje na formação social em que vivemos, os indicativos apontam na direção de que os sujeitos pensam, projetam, criam e alargam os limites de seus tempos e de seus espaços de experimentação do lazer, ressignificando-os em algo que parece não caber mais apenas sob essa denominação.